AN ASSESSMENT OF PERCEPTION OF THE PEOPLE ON MALARIA PREVENTION AND CONTROL IN DONGA LOCAL GOVERNMENT AREA OF TARABA STATE - SILAS JOSHUA; SUNDAY EMMANUEL BAMISE (International Studies Journal)
The study examined household’s knowledge, attitude and practice on Malaria prevention and control in Donga L.G.A of Taraba State. A total of 120 respondents representing 120 households were used for the study. Primary data were generated through administration of structured questionnaire. The types of data used are demographic data, socio-economic, cultural beliefs, political affiliations and prevalent records of malaria in the area. Data analysis was done using tables, percentages, and charts. Chi Square was used for the analysis via micro excels. Findings show that respondents have good knowledge about malaria in the study area. (60%) are men (40%) are female representing households during the research. Households’ knowledge, attitudes and practice on malaria prevention and control were found to vary from household to household based on the socio-demographic characteristics of the respondent. However, (33.33%) were age 15-24 years, (35.83%) were age 25-34 years, (17.5%) were age 35-44 years, (12.5%) were 45-54 years and (0.83%) were 55 above. Generally, (78.33%) believed that mosquitoes can transmit malaria to human while (67.5%) of the respondents’ household have mosquitoe nets, also (56.67%) opined that mosquitoes net are often used by the respondents. The study identified other protective practices against mosquito’s bites and further assessed whether such practices do affect insecticide treated net (ITN) usage. The study recommends that in a bit to improve malaria control measures, community members need to be educated on the relationship between mosquitoes and malaria, and the benefits of accepting cost effective preventive measures including early seeking of treatment from the health facilities or health personnel. There is a need for health education programs that will measure the success of the health education message passed to the community and evaluation of the health education provided to assess the impact of the message among the community members.